TRANSBOUNDARY HAZE POLLUTION IN THE ASEAN REGION: AN ASSESSMENT OF THE ADEQUACY OF REGIONAL AND NATIONAL LEGAL FRAMEWORK IN INDONESIA - Nurhidayah, Laely (Jurnal Masyarakat dan Budaya, 2014)
Haze pollution is one of the major environmental problems in the ASEAN region. Every year in dry season, forest fires occur in Indonesia creating havoc at domestic level and regionally affected neighbouring countries. This fire is caused by human activities in burning land/forest for plantation and/or agriculture. This paper argues that transboundary haze pollution cannot be solved solely on a regional level.It needs comprehensive efforts and co-operation from regional, international, national and local level. An improvement on both regional and national legal framework and law enforcement in addressing haze pollution problem is needed.